Improving the Energy Efficiency of Direct Formate Fuel Cells with a Pd/C-CeO2 Anode Catalyst and Anion Exchange Ionomer in the Catalyst Layer - Hamish Andrew Miller; Jacopo Ruggeri; Andrea Marchionni; Marco Bellini; Maria Vincenza Pagliaro; Carlo Bartoli; Andrea Pucci; Elisa Passaglia; Francesco Vizza (Energies, 2018)
This article describes the development of a high power density Direct Formate Fuel Cell (DFFC) fed with potassium formate (KCOOH). The membrane electrode assembly (MEA) contains no platinum metal. The cathode catalyst is FeCo/C combined with a commercial anion exchange membrane (AEM). To enhance the power output and energy efficiency we have employed a nanostructured Pd/C-CeO2 anode catalyst. The activity for the formate oxidation reaction (FOR) is enhanced when compared to a Pd/C catalyst with the same Pd loading. Fuel cell tests at 60 °C show a peak power density of almost 250 mW cm−2. The discharge energy (14 kJ), faradic efficiency (89%) and energy efficiency (46%) were determined for a single fuel charge (30 mL of 4 M KCOOH and 4 M KOH). Energy analysis demonstrates that removal of the expensive KOH electrolyte is essential for the future development of these devices. To compensate we apply for the first time a polymeric ionomer in the catalyst layer of the anode electrode. A homopolymer is synthesized by the radical polymerization of vinyl benzene chloride followed by amination with 1,4-diazabicyclo[2.2.2]octane (DABCO). The energy delivered, energy efficiency and fuel consumption efficiency of DFFCs fed with 4 M KCOOH are doubled with the use of the ionomer.